Mortality and admissions for cerebrovascular and cardiovascular diseases after the Accumoli-Amatrice 2016 earthquake. - Chiara Cadeddu; Mario Cesare Nurchis; Carolina Castagna; Martina Sapienza; Rosaria Messina; Stefano Marchetti; Walter Ricciardi; Aldo Rosano (PLoS ONE)
Objective The aim of this study is to evaluate if the mortality and hospital admissions for cerebrovascular and cardiovascular diseases (CCVDs), with a specific focus on acute myocardial infarction (AMI), significantly increased within 12 months after the 2016 Accumoli-Amatrice earthquake in the 17 most hit municipalities. Methods A diff-in-diff regression model was applied to the annual occurrences to assess the differences in the mortality and hospitalization for selected CCVDs before and after the Earthquake in the area most hit by the earthquake compared to a surrounding area. A focus analysis on acute myocardial infarction (AMI) was performed. Results The analysis of mortality showed a significant increase in the death rate for AMI in the year immediately following the earthquake with +1.7 cases per 10,000 (95% CI: 1.53-1.87). A significantly increased number of hospital admissions and deaths for AMI was also noticed. Conclusions Evaluating the epidemiology of CCVDs events related to natural disasters, might contribute to provide information for the population dealing with future events and can be used to improve preparedness in rescue and life-saving medical interventions during and after the earthquake.